Evaluation of molluscicidal activity of Gymnema sylvestre R. Br., (Asclepiadaceae) - Brustolin, Andréa (2008)
Gymnema sylvestre R. Br. (Asclepiadaceae) is a native plant found in India. The leaves are used in folk medicine as antidiabetic, stomachic, diuretic, astringent and tonic. The methanolic extract and fractions obtained from aerial parts were used to evaluate the molluscicidal activity against the snail (Biomphalaria glabrata). The methanolic extract and its fractions were analyzed by thin-layer chromatography, foam and the hemolitic index were measured, and the physical and chemical characteristics of aerial parts of this species were analyzed. The methanolic extract yielded five fractions, the methanolic fraction presented moluscicidal activity against Biomphalaria glabrata and showed content of hemolitic compound by thin-layer chromatography